Innovation Networks Modeling within the Concept of Open Innovations - Irina A. Zaraychenko; Aleksey I. Shinkevich; Mikhail Y. Shvetsov; Klavdiya G. Erdyneyeva; Lidiya A. Bordonskaya; Aleksandra E. Persidskaya; Sofya A. Rozhkova; Aleksandr A. Afanasyev (International Journal of Economics and Financial Issues, 2016)
The urgency of the problem discussed in the article is caused by necessity to search for effective forms of innovation activities' implementation, providing a maximizing of innovative resources' impact by strengthening relationships between entities of the innovation process. The purpose of the article is to develop a model of innovation network, facilitating the acceleration of the diffusion of innovation by increasing its throughput capability and maximum use of the resources of the state innovation system. The leading approach to the study of this problem is the system approach, according to which the interaction of entities in the innovation process is considered as a complex mechanism of communications, ensuring the transformation of innovative ideas into marketable final product. In this paper, a model of innovation network, meeting the requirements of the concept of open innovation, based on the effect of increasing returns of resources is proposed and the mechanism and the necessary conditions for its functioning are described. The materials presented in the paper can be used to develop long-term development programs, both locally and at the regional and Federal levels, while building the innovative systems of the appropriate level and providing adequate conditions for their functioning.